An Investigative Study of Diffusion of Commercial Aspirin (Acetylsalicylic acid) in Sodium - Anditi , Collins; Okoth , Maurice; Muthoka , Titus M.; Irina , Justin; Kipkosgei , Moses (African Journal of Education,Science and Technology (AJEST), 2025)
Diffusion is a macroscopic motion of components of a system that arises from concentration difference. Reaction diffusion is widely used to model developmental process. This project considers effective mechanism leading to effective diffusion coefficient. A mathematical formalism for transforming local transport law into diffusive terms is developed. The diffusion coefficient of drug aspirin was studied in basic NaOH of concentration range 0.01 to 0.1M at 25 oC. The rate of diffusion was monitored by observing the boundary conditions of the indicator between the drug and solution. In the study five (5) aspirin tablets collected from a local pharmacy in Eldoret town were used for the study. From the profile it was observed that as the time progressed the boundary increased fast for non-coated tablets compared to the coated ones. All the aspirin were found to give values according to underlying mechanism. For the drug A (600mg) of aspirin the best value of diffusion coefficient of 1.69 x 10 -4 cm2 sec-1 was observed while the values for coated drug E with 75 mg aspirin was found to be slightly lower. Fickian mechanism is believed to be the consequence of drug molecule small size. First of all fractional drug uptake is linear and independent of the sample of thickness when In [NaOH] is plotted against square distance. A graph of x2 against In [NaOH] was plotted which was used to calculate the diffusion coefficient. The experimental values of diffusion coefficient Do were within the experimental error to those of (4Dt) -1. The study also adopted a descriptive case study; it was conducted at Kimumu municipality, Eldoret town. The target population consisted of 25 respondents. Data was collected using self-administered questionnaires and interview schedules, coded and analysed usin g SPSS version 16.0. Systematic quantitative review data was analysed using means and frequency tables and percentages while qualitative data was analyzed using inferential statistics chi -square. Data was presented using table, pie charts and graphs. The study found that most of the individuals preferred drug B.